Overestimation of Astrophysical Gamma-Ray Energies during Thunderstorms: Synergy of Galactic and Atmospheric Accelerators - A. Chilingarian; M. Zazyan (The Astrophysical Journal Letters)
Particle accelerators abound in space plasmas, saturating the cosmos with fully stripped nuclei and gamma rays, with energies surpassing the capabilities of human-made accelerators by orders of magnitude. Upon reaching Earth’s atmosphere, these particles trigger extensive air showers (EASs), generating millions of secondary cosmic rays of lower energies. Free electrons from EASs developing in the atmosphere are seeds for atmospheric electron accelerators. Strong atmospheric electric fields (AEFs) evolving during thunderstorms act as accelerators, amplifying the intensity of electrons many times, significantly enlarging the EAS size (number of electrons). Thus, the energy of the primary cosmic ray recovered by EAS size can be significantly overestimated. Recently discovered by high-altitude EAS arrays, PeVatron candidates (ultra–high-energy (UHE) astrophysical gamma-ray sources) must be carefully examined according to the atmospheric conditions during EAS detection. Large High Altitude Air Shower Observatory and High-Altitude Water Cherenkov Observatory arrays are located in regions of frequent thunderstorms, and an AEF’s strength can reach and surpass the critical strength to start relativistic runaway electron avalanches. A few registered UHE gamma rays from stellar sources can be registered at just this time when the AEF highly enhances the EAS size. Thunderstorm ground enhancements are copiously registered at mountain peaks of Eastern Europe, Germany, and Armenia, with energies well above the threshold energy of EAS array scintillators. Thus, the overestimation of the energy of primary particles is not an exotic process but a consequence of already well-established physical phenomena. Consequently, a report on each registered UHE gamma ray should include the recorded time and corresponding weather conditions.